Molecular and structural mechanisms of ZZ domain‐mediated cargo selection by Nbr1. (25th June 2021) - Wang, Ying‐Ying; Zhang, Jianxiu; Liu, Xiao‐Man; Li, Yulu; Sui, Jianhua; Dong, Meng‐Qiu; Ye, Keqiong; Du, Li‐Lin
Abstract: In selective autophagy, cargo selectivity is determined by autophagy receptors. However, it remains scarcely understood how autophagy receptors recognize specific protein cargos. In the fission yeast Schizosaccharomyces pombe, a selective autophagy pathway termed Nbr1‐mediated vacuolar targeting (NVT) employs Nbr1, an autophagy receptor conserved across eukaryotes including humans, to target cytosolic hydrolases into the vacuole. Here, we identify two new NVT cargos, the mannosidase Ams1 and the aminopeptidase Ape4, that bind competitively to the first ZZ domain of Nbr1 (Nbr1‐ZZ1). High‐resolution cryo‐EM analyses reveal how a single ZZ domain recognizes two distinct protein cargos. Nbr1‐ZZ1 not only recognizes the N‐termini of cargos via a conserved acidic pocket, similar to other characterized ZZ domains, but also engages additional parts of cargos in a cargo‐specific manner. Our findings unveil a single‐domain bispecific mechanism of autophagy cargo recognition, elucidate its underlying structural basis, and expand the understanding of ZZ domain‐mediated protein–protein interactions. SYNOPSIS: Schizosaccharomyces pombe Nbr1 belongs to an ancient protein family that confers selectivity to autophagy in eukaryotes. This study identifies two novel protein cargos targeted to the vacuole by Nbr1 and reveals the mechanisms underlying their recognition in fission yeast. Nbr1 promotes the vacuolar targeting of Ams1 and Ape4 hydrolases. Ams1 and Ape4 bind to the first ZZ domain of Nbr1 (Nbr1‐ZZ1) in a mutually exclusive manner. Cryo‐EM analysis shows that the N‐termini of Ams1 and Ape4 interact with the same binding pocket in Nbr1‐ZZ1. Non‐N‐terminal regions of Ams1 and Ape4 make contact with Nbr1‐ZZ1 at cargo‐specific binding interfaces. Abstract : High‐resolution cryo‐EM analyses reveal how the adaptor protein Nbr1 specifically recognizes two novel cargoes during selective autophagy in Schizosaccharomyces pombe .